A Survey of the Pain Experienced by Males and Females with Fabry Disease - Andrea L Gibas; Regan Klatt; Jack Johnson; Joe TR Clarke; Joel Katz (Pain Research and Management)
BACKGROUND: The clinical onset of Fabry disease, a rare, X-linked, multisystemic disorder, is marked by neuropathic pain. Males suffer extensively from this disease. Females, as genetic ‘carriers’, have traditionally been viewed as either asymptomatic or mildly afflicted with this disease.